Safety behavior model based on safety competence, culture, and awareness - Prasetiawan, Saptana Tri; Ahmad, Irdham; Setyawati, Aswanti; Zainal, Munawaroh (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Safety behavior is crucial to reducing the potential for ship accidents. Therefore, the research focuses on investigating and finding an empirical model of the influence of safety competence and safety culture on crew safety behavior through safety awareness. The research uses a quantitative approach with survey methods and causal design. The sample was 250 crew members. The research instrument used was a questionnaire designed as a Likert scale with five options for responses. The questionnaire was distributed in Google Form format via the WhatsApp application. The data were analyzed using structural equation modeling (SEM). The research results show that safety competence, safety culture, and safety awareness have a significant effect on safety behavior; safety competence and safety culture have a significant effect on safety awareness; and safety competence and safety culture significantly affect safety behavior through safety awareness. These findings promote a new empirical model of the effect of safety competence and safety culture on crew safety behavior through safety awareness. This new model deserves critical discussion by researchers, academics, and practitioners before being adopted, adapted, or modified for their future work in the future.